D. P. Juravskyi: the First Ukrainian Theorist of Statistical Science (in memory of the 160th anniversary of his death) - Chekotovskyi Е. V. (Statistics of Ukraine, 2016)
The contribution to the development of statistical science of the prominent Ukrainian theorist-statistician of the first half of XIX century Dmytro Petrovych (1810-1856) is discussed. It is emphasized that D. Juravskyi is the first Ukrainian statistical theorist who contributed profoundly in the scientifically grounded approach to classifying statistics as a science and in its methodology. Extensive review of his book “On Sources and Use of Statistical Information”, published 170 years ago in August, 1846, in Kyiv, is given. As one of the best and original works on theoretical statistics, this book is still important today. It was highly appreciated by the distinguished statistical scientists of the Russian Empire. Soviet and Russian statisticians also referred to the prominent role of D. Juravskyi in the history of Russian statistical science and even called him the founder of Russian statistical science and Russian theoretical statistics. It is emphasized that today D. Juravskyi is described in Russian literature on science and education as a prominent Russian scientist. Evidences are given to demonstrate that D. Juravskyi can be appropriately qualified as a genuine Ukrainian statistician. Theoretical principles of statistical science, expounded by D. Juravskyi in three sections of his book, are highlighted. The first section of the book is devoted to statistics as a science, its general significance, the need for critical review of the applied tools, significance of statistical studies for government and public, for various social classes, statistical studies of morality and education of the population, etc, D. Juravskyi notes that statistics of that period, being at very low level, could not be qualified as a science. He was the first one in the history of Russian statistics to discuss authenticity of statistical data and their adequacy for economic analysis. He criticizes the official sources of statistical data as unreliable. Juravskyi was the first in the Russian statistical literature to emphasize the necessity and importance of budgetary inspections. In the second section of the book, D. Juravskyi made critical review of the sources of statistical data in the Russian Empire, pointed out to their incompleteness and unreliability, scarified the unreliability of metrical books and other sources of statistical information and showed the ways for their proper arrangement. In the third section, D. Juravskyi defines the general object and method of statistics as a science, gives extensive characteristic to the statistical science in Russian Empire of his and earlier time, proposes specific ways and facilities for proper arrangement of statistical services, defines the objective of the central statistical authority, demonstrates his conception of the integrated statistical system etc.